Remaking the American Dream : The Informal and Formal Transformation of Single-Family Housing Cities - Mukhija, Vinit (Cambridge, Massachusetts : The MIT Press, 2022)
A critical examination of how single-family housing, the building block of US cities, is changing and its transformative potential for American urbanism
Keywords: Urbanization--United States; Housing, Single family--United States; American Dream